University of South Florida College of Public Health: Reflections on Doctoral Education 1987 - 2005 - Karen M. (Kay); Robert J. McDermott (University of North Florida, 2005)
The establishment of doctoral training is a milestone in the chronological and intellectual development of an academic institution. The University of South Florida College of Public Health (COPH) admitted its first doctoral student in the fall of 1987 and graduated its first two in 1992. The USF COPH will top the century mark in PhD graduates in 2005. This article summarizes the history of doctoral education at the USF COPH and provides highlights of a few of the nearly 100 PhD graduates now making a mark on improvement of public health research, education, and practice - in Florida, and elsewhere.